Clinical-epidemiologic aspects of patients with tuberculosis, Guantánamo 2013-2018 - Betsy Donatien-González; Caridad Franklin-Santel; Lourdes Margarita Expósito-Boue (Revista Información Científica, 2023)
Introduction: despite the scientific efforts to eliminate tuberculosis, it is currently considered as a reemerging disease. In Guantánamo province, no research closely related to the subject was found.